Factors influencing sustained competitive advantage among telecommunication firms in Malaysia - Muthu, Devandran (2019)
With the emergence of the digital economy and shorter product/service life cycles, advanced knowledge in the field of sustained competitive advantage has become critical. This study expands the knowledge by integrating broad based theories for empirical testing. Four theories, namely, the Resource-Based Theory, Dynamic Capabilities Theory, Diffusion of Innovation Theory and Social Exchange Theory were integrated to examine factors relating to sustained competitive advantage in the telecommunication industry in Malaysia. A conceptual framework was formulated with these factors: a) Firm Agility (alertness, accessibility, decisiveness, swiftness, and flexibility), b) New Product Development (design thinking, human-computer interaction, design engineering, software development), c) Innovation (magnitude & speed), with the focal construct being sustained competitive advantage to achieve customer retention. Additional postulates included Disruptive Technology as moderator; and Customer Loyalty as mediator. This was a quantitative study adopting the survey method and data were collected from the Malaysian telecommunication service providers (TSPs) and analyzed using SPSS and Smart PLS 3. The findings revealed that three factors had significant positive relationships with the focal construct; and both the moderator and mediator significantly affected the focal construct, leading towards achieving customer retention. The results imply that customer loyalty is an important component in the creation of competitive advantage for customer retention. The results also indicated that disruptive technology is a strong influence on customer loyalty. Consequently, the vigilance of TSPs towards new technologies is vital to move technological breakthroughs from incubators to mainstream; and to sustain customer loyalty. The results of this study provide better understanding of the factors that are relevant to customer retention.